2017
DOI: 10.1371/journal.pone.0171039
|View full text |Cite
|
Sign up to set email alerts
|

Ligand binding at the A-cluster in full-length or truncated acetyl-CoA synthase studied by X-ray absorption spectroscopy

Abstract: Bacteria integrate CO2 reduction and acetyl coenzyme-A (CoA) synthesis in the Wood-Ljungdal pathway. The acetyl-CoA synthase (ACS) active site is a [4Fe4S]-[NiNi] complex (A-cluster). The dinickel site structure (with proximal, p, and distal, d, ions) was studied by X-ray absorption spectroscopy in ACS variants comprising all three protein domains or only the C-terminal domain with the A-cluster. Both variants showed two square-planar Ni(II) sites and an OH- bound at Ni(II)p in oxidized enzyme and a H2O at Ni(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…A prominent backscattering peak owing to the Ni p –Ni d and Ni p –Fe contributions is also present in the second shell of the Fourier-transform Ni EXAFS, which was also fit to 2.98 Å, confirming the proper metal loading at the active site. Additionally, sharpening of the Ni K-rising-edge feature on conversion of A Ox to A Me is consistent with increasing planarity at the Ni sites suggested by theoretical calculations (see below) that show that the planarity of Ni d remains unaltered while Ni p approaches a square-planar configuration upon methyl binding. It is important to note here that our XAS results contrast with prior XAS studies of the A Me form of Carboxydothermus hydrogenoformans ACS, which showed a rising-edge shifted to lower-energy relative to A Ox , and assignment of a weak ∼2.4 Å Ni–Me, bound in the apical position of a square pyramid. The study lacks from supporting kinetic or spectroscopic quantification of the percentage methylation as well as the extent of metal loading at the Ni p , Ni d , and [4Fe–4S] 2+ cluster sites and comparison with the data presented here suggest only modest methylation in the experiments on the C.…”
Section: Resultssupporting
confidence: 86%
“…A prominent backscattering peak owing to the Ni p –Ni d and Ni p –Fe contributions is also present in the second shell of the Fourier-transform Ni EXAFS, which was also fit to 2.98 Å, confirming the proper metal loading at the active site. Additionally, sharpening of the Ni K-rising-edge feature on conversion of A Ox to A Me is consistent with increasing planarity at the Ni sites suggested by theoretical calculations (see below) that show that the planarity of Ni d remains unaltered while Ni p approaches a square-planar configuration upon methyl binding. It is important to note here that our XAS results contrast with prior XAS studies of the A Me form of Carboxydothermus hydrogenoformans ACS, which showed a rising-edge shifted to lower-energy relative to A Ox , and assignment of a weak ∼2.4 Å Ni–Me, bound in the apical position of a square pyramid. The study lacks from supporting kinetic or spectroscopic quantification of the percentage methylation as well as the extent of metal loading at the Ni p , Ni d , and [4Fe–4S] 2+ cluster sites and comparison with the data presented here suggest only modest methylation in the experiments on the C.…”
Section: Resultssupporting
confidence: 86%
“…The data in Table 6 for protonation on the hydroxyl ligand in A ox and A red1 shows that pK a values are relatively low for the oxidized form and high for one-electron reduced form. This is in accordance with the experimental findings that the oxidized form has a hydroxyl ligand and one-electron reduced a water one [56]. The pK a values for A red2 with ligands are quite large and significantly lower for the dielectric constant 80.…”
Section: Pk Asupporting
confidence: 91%
“…At the same time, it can be found that the Ni p -Fe1 distance is very small (2.243 Å) in the PDB ID: 6YTT crystal structure [46] where there is no ligand on Ni p and in turn very long in the crystal structure PDB ID: 6X5K [36] with the carbonyl ligand. This is not the case in the EXAFS results for the CO ligand, where this distance is equal to 2.80 Å [56] (Table 2). If we look at the Ni p -Fe1 distances obtained from the calculations, it can be seen that the M1 model with CO gives values similar to the crystal structure and the M2 model to EXAFS [56]; however, both calculated values are longer than in the experimental case.…”
Section: Structural Propertiesmentioning
confidence: 78%
See 2 more Smart Citations